Penegakan Hukum Pidana terhadap Illegal Logging: Kajian dalam Perspektif Hukum Positif dan Hukum Islam - Nasir, Nasir Wirawan Sinaga; Sodikin, Sodikin (Journal of Contemporary Law Studies, 2025)
This study aims to analyze the enforcement of criminal law against illegal logging from the perspective of positive law, particularly Law Number 18 of 2013 on the Prevention and Eradication of Forest Destruction, and Islamic law, which emphasizes ethical principles such as maslahah (public welfare), hifz al-bi'ah (environmental preservation), and hifz al-mal (protection of property). This research employs a qualitative method with a normative and comparative approach, utilizing literature studies and legal analysis. The findings reveal that positive law enforces strict legal sanctions, including imprisonment of up to 10 years and fines of up to 5 billion rupiah, to create a deterrent effect. Meanwhile, Islamic law emphasizes moral responsibility and social awareness, viewing illegal logging as a breach of divine and social trust. Both legal frameworks recognize illegal logging as a criminal act and provide various penalties, including ta’zir in Islamic law. However, the effectiveness of law enforcement depends on government consistency and public participation. This study recommends integrating Islamic legal values with positive law to develop a more comprehensive, value-based, and sustainable legal framework for combating illegal logging.